2021
DOI: 10.1017/mem.2021.3
|View full text |Cite
|
Sign up to set email alerts
|

Media, technology, and the sins of memory

Abstract: Human memory is prone to error and distortion. It has been proposed that memory's misdeeds can be classified into seven categories or ‘sins’. This article discusses the impact of media and technology on four memory sins: transience (forgetting over time), absent-mindedness (lapses in attention that produce forgetting), misattribution (attributing a memory to the wrong source), and suggestibility (implanted memories). Growing concerns have been expressed about the negative impact of media and technology on memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 84 publications
2
19
0
2
Order By: Relevance
“…In Experiment 2, designed specifically for ease and to afford individuals every opportunity to perform to their full potential, we observed collaborative inhibition. Our explanation of a reverse social loafing effect is consistent with evaluations of the ways in which constant access to online media and digital technology can create memory lapses and distortions where, for example, media multitasking can produce attentional lapses and undermine memory for target information (Marsh and Rajaram 2019; Schacter 2022; Wammes et al 2019)…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In Experiment 2, designed specifically for ease and to afford individuals every opportunity to perform to their full potential, we observed collaborative inhibition. Our explanation of a reverse social loafing effect is consistent with evaluations of the ways in which constant access to online media and digital technology can create memory lapses and distortions where, for example, media multitasking can produce attentional lapses and undermine memory for target information (Marsh and Rajaram 2019; Schacter 2022; Wammes et al 2019)…”
Section: Discussionsupporting
confidence: 83%
“…The study of memory in the digital age from a cognitive psychology perspective is relatively new, and it has sparked a profound debate about exactly how the Internet, for better or for worse, has impacted human memory (eg, Carr 2008; Schacter 2022). While there is a plethora of studies that have revealed the nature of human memory, and social memory, most of these studies have been conducted in-person outside the context of the Internet and technology (Rajaram and Marsh 2019).…”
Section: Online Social Rememberingmentioning
confidence: 99%
“…A likely explanation is that he integrated the vivid and memorable images of the first plane crash, which were widely broadcast in the media in the days following the attack, into his own memory. This example shows how suggestible our memory can be, but also how the media can influence it (Schacter 2022).…”
Section: Collective Memory Studies: Across Disciplines and Across Gen...mentioning
confidence: 99%
“…However, in relation to digital media and technology, the slowly emerging evidence does not support simple conclusions. Instead, it paints a complex picture of different effects that are dependent on different factors (Schacter 2022).…”
Section: Ecological Validitymentioning
confidence: 99%